On the structure of the general solution of a degenerate linear system of second-order differential equations - Yakovets, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish sufficient conditions for the existence of a general Cauchy-type solution and conditions for the solvability of the Cauchy problem for a system of second-order differential equations.